2006
DOI: 10.1190/1.2181309
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis effects studied by numerical simulations: Cyclic loading-unloading of a realistic sand model

Abstract: When Hertz-Mindlin force laws are considered in the context of the effective-medium theory, the predictions yield a constant Poisson coefficient and bulk/shear elastic moduli that scale with pressure with a 1/3 power law exponent (P 1/3 ). This prediction contradicts early and recent experimental findings that conclude moduli grow faster with a 1/2 power law exponent (P 1/2 ). Such a conclusion is also reached by recent second-order corrections to linear elastic theory. In this work we use a discrete-particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 18 publications
(33 reference statements)
2
26
0
Order By: Relevance
“…() confirm the HM model prediction of bulk modulus of glass beads with experimental data using an empirical dependence of coordination number, that is, the average number of grains in contact, and porosity on pressure from numerical simulations (Zhang and Makse ). Garcia and Medina () confirm the dependence of coordination number and porosity to the hydrostatic pressure and thus validate the HM model. Zimmer et al .…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…() confirm the HM model prediction of bulk modulus of glass beads with experimental data using an empirical dependence of coordination number, that is, the average number of grains in contact, and porosity on pressure from numerical simulations (Zhang and Makse ). Garcia and Medina () confirm the dependence of coordination number and porosity to the hydrostatic pressure and thus validate the HM model. Zimmer et al .…”
Section: Introductionsupporting
confidence: 57%
“…Garcia and Medina () have shown that this power law fits coordination and porosity results in their relationship for glass beads: Cfalse(Pfalse)=C0+9.7(φ0φfalse(Pfalse))0.48.These geometrical parameters are empirically estimated from the simulation of random spherical packs. Zimmer et al .…”
Section: Theorymentioning
confidence: 95%
See 1 more Smart Citation
“…The coordination number n' is reduced for the static loading condition (Takahashi and Tanaka 2010) and is modeled using the power-law relation by Garcia and Medina (2006):…”
Section: Analytical Evaluationmentioning
confidence: 99%
“…Makse et al (2005) obtained CN as a function of pressure for both two and three dimensional cases from simulation results and found a critical minimal value of 4 and 6 respectively. Garcia and Medina (2006) used numerical simulation and got different CN in loading and unloading cycles as a function of pressure and porosity. Zimmer et al (2007a) rewrote the trend of CN as a function of porosity from the data compiled by Murphy (1982).…”
Section: Introductionmentioning
confidence: 99%